Nanomaterials to relieve tumor hypoxia for enhanced photodynamic therapy. (December 2020) - Zhang, Cheng; Qin, Wen-Jun; Bai, Xue-Feng; Zhang, Xian-Zheng
Graphical abstract: This review summarizes recent research progress in versatile nanomaterials for enhanced photodynamic therapy by relieving tumor hypoxia. Highlights: This review summarizes recent progress in nanomaterials for enhanced photodynamic therapy by relieving tumor hypoxia. The methods for constructing these nanomaterials based on characteristic factors in tumor are discussed. The limitations and prospects of nanomaterials for enhanced photodynamic therapy are also discussed. Abstract: Photodynamic therapy (PDT) shows great potential for tumor treatment owing to its high spatiotemporal selectivity, minimal invasiveness and patient compliance. However, the therapeutic effect of PDT is seriously hindered by the tumor hypoxia in vivo. Hypoxia is a typical hallmark of the solid tumor microenvironment, which promotes the proliferation, invasion and metastasis of tumor cells. Additionally, the oxygen consumption during PDT will further aggravate the tumor hypoxia, resulting in multiple undesirable side-effects. To resolve these problems, many studies have been conducted to improve the efficacy of PDT by increasing oxygen concentration in tumor. Here, we focus on the current advances in nanomaterials-mediated tumor oxygenation via oxygen-carrying or oxygen-generating strategies to relieve tumor hypoxia. Based on the comprehensive overview, we hope these inspirations in hypoxia-associated anti-tumor therapy will provide perspectives in designing new oxygenation nanomaterials in this promising field.